Ukraine : 2006 Article IV Consultation; Staff Report; Staff Statement; and Public Information Notice on the Executive Board Discussion. (IMF Staff Country Reports; Country Report ;, 2007)
This 2006 Article IV Consultation highlights that Ukraine's fiscal policy in 2005-06 reshuffled resources from higher saving businesses to lower saving households, touching off a consumption boom, which has been reinforced by rapid credit expansion. In 2005, this boom helped to offset the drag on the economy from marked real currency appreciation, weaker steel exports owing to intensified third-country competition, higher business-tax collections, and post-Orange-Revolution reforms, which clamped down on tax loopholes, smuggling, and corruption. The authorities have proven adept at hitting low fiscal deficit targets.